2011
DOI: 10.1007/s11920-011-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Update on Attention-Deficit/Hyperactivity Disorder and Tic Disorders: A Review of the Current Literature

Abstract: Tic disorders impact quality of life, but when they are co-occurring with attention-deficit/hyperactivity disorder, the combined impact takes a toll on psychosocial functioning and adds another layer of complexity to treatment approaches. A review of the current literature supports evidence of a unique relationship between comorbid attention-deficit/hyperactivity disorder and tic disorders, emphasizing the intricate phenotype and impairment associated with these co-occurring conditions. The complexity of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 56 publications
0
8
0
3
Order By: Relevance
“…Tics characteristically present with a wide range of severity, from mild twitches that go unnoticed to forceful movements and loud noises that cause injury and call other people’s attention {10}. Moreover, 90% of patients present with co-morbid psychiatric disorders {3133}, most commonly obsessive-compulsive disorder (OCD) {3436} and attention-deficit and hyperactivity disorder (ADHD) {37,38}, although both affective disorders {39,40} and impulse control disorders {4143} have also been shown to be associated with TS. Disease-specific health-related quality of life measures for patients with TS {44} have allowed a more accurate assessment of the differential impact of tics and behavioral symptoms on patients’ wellbeing {45}.…”
Section: Clinical Phenomenology Of Ticsmentioning
confidence: 99%
“…Tics characteristically present with a wide range of severity, from mild twitches that go unnoticed to forceful movements and loud noises that cause injury and call other people’s attention {10}. Moreover, 90% of patients present with co-morbid psychiatric disorders {3133}, most commonly obsessive-compulsive disorder (OCD) {3436} and attention-deficit and hyperactivity disorder (ADHD) {37,38}, although both affective disorders {39,40} and impulse control disorders {4143} have also been shown to be associated with TS. Disease-specific health-related quality of life measures for patients with TS {44} have allowed a more accurate assessment of the differential impact of tics and behavioral symptoms on patients’ wellbeing {45}.…”
Section: Clinical Phenomenology Of Ticsmentioning
confidence: 99%
“…Around 90% of patients with TS are diagnosed with co-morbid psychiatric disorders [16,18,19]. The most common behavioral co-morbidities are obsessivecompulsive disorder [20,21] and attention deficit and hyperactivity disorder [22,23], although affective disorders [24] and impulse control disorders [25][26][27] have been reported more commonly in patients with TS than in the general population.…”
Section: Tourette Syndromementioning
confidence: 99%
“…Accordingly, treatment designed based on the defects of executive functions and sensory integration has stronger theoretical foundations. Since studies suggest that reduction of multi-dimensional problems of ADHD is feasible to be done through, incorporating some treatment approaches (Simpson et al, 2011). Thus due to problems in executive functions and sensory integration, the present research is trying to cause stimulation and neuroplasty of more and wider areas of the brain by doing activities that have a direct impact on attention, working memory, behavioral inhibition (components of executive functions of the brain), and sensory problems, problems with balance (sensory integration components).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study by Ibrahimi (2013) showed that sensory-motor integration intervention with an emphasis on proprioceptive and vestibular senses (twice a week and during 12 sessions of two hours) significantly improved ADHD. Access to treatment with the most effectiveness encourages the researchers for further studies, and as studies suggest multi-dimensional problems of ADHD is possible by incorporating some treatment approaches (Simpson et al, 2011). Due to the effectiveness of the treatments based on executive functions of the brain and sensory integration, this study plans to study the effectiveness of combining two therapeutic methods "executive functions" and "sensory integration," both of which are treatments with considerable research evidence and emphasize neurocognition factors.…”
Section: Introductionmentioning
confidence: 99%